Effect of layer height, infill geometry, nozzle temperature, and fan speed on tensile strength of 3D printing PETG specimens - Mahatma Junjung Mardlotila; Muhammad Trifiananto; Hari Arbiantara Basuki; Muh Nurkoyim Kustanto; Intan Hardiatama; Dedi Dwilaksana (Universitas Negeri Padang, 2022)
This research is aimed to provide insight on the dependency of tensile strength on process parameters of the Fused Deposition Modeling (FDM). FDM is one of the most popular 3D printing manufacturing techniques. In the present study, a tensile test was performed to measure the tensile strength of PETG (Polyethylene terephthalate glycol) specimen with the combination of different layer height, infill geometry, nozzle temperature, and fan speed whereas other parameters are kept at a constant level. This study uses the ISO 527 1BA standard. Taguchi L16 (44) with 4 levels for each factor was used to determine the effect of each parameter. Each experiment repeated 3 times to minimize the occurrence of errors. layer height, infill geometry, nozzle temperature, and fan speed ​​respectively effect of 13.4%, 63.6%, 19.0%, and 2.7%. Fan speed is considered a parameter that has no impact on tensile strength. The layer height and nozzle temperature parameter shows that the higher the value, the tensile strength of specimens tend to increase. Furthermore, infill geometry from the one with the highest to the lowest tensile strength value is gyroid, zig-zag, grid, and triangles. The combination of layer height of 0.24 mm, infill geometry gyroid, and nozzle temperature of 250 ˚C is the optimum combination of parameters which has the highest tensile strength of 34.76 N/mm2.